Anti-angiogenesis in human lymphomas. New insights - Ribatti, Domenico; Tamma, Roberto; Ingravallo, Giuseppe; Specchia, Giorgina (Frontiers in Oncology, 2025)
Targeting tumor angiogenesis is an advancement in the treatment of hematological malignancies. This article summarizes the most recent advancements in the use of anti-angiogenic agents in the treatment of human lymphomas. Preclinical and clinical studies have evidenced that treating lymphomas with anti-angiogenic monotherapy may not be successful. Alternative therapeutic strategies may be used to overcome resistance to anti-angiogenic therapy, including the association of different anti-angiogenic molecules or their combination with other treatment regimens.